TRANSPARENCY AND ACCOUNTABILITY IN HEALT-CARE SERVICES FROM NURSE MANAGERS' PERSPECTI-VE: A QUALITATIVE STUDY - Hüseyin ABUHANOĞLU (Fırat University, 2019)
In recent decades, as in all sectors, health sector has been characterized by increasing calls for accountability and transparency. Especially in recent years, transparency and accountability began to take place between the dimensions of perceived service quality in health care and to shown as key elements in modern management theory and practices. “What are being aimed in health services”. This study which was performed moved from this question. The aim of this study was emphasize the importance of the transparency and accountability in health care management. In recent years these concepts have considered as the current approaches in health care. For this purpose, it was interviewed with 70 nurse managers working in 42 departments of a training hospital in Ankara about transparency and accountability in health care. All of the nurse managers stated that health care should be transparent, but 70 percent of managers expressed health care are not transparent. When evaluated views on the account of health care accountability, the vast majority of nurse managers (83%) stated that health care should be accountable, but 87 percent of managers expressed health care not accountable. According to managers views, basic elements ensuring transparency in health care are effective communication, clearly determination of roles and responsibilities, respect for patients’ rights and patient-centered services delivery and personnel training. Moreover, it was found that basic elements ensuring accountability in health care are clearly determination of roles and responsibilities, effective communication, personnel training and transparency. It should be clearly defined roles and responsibilities, should be given lectures on communication to all staff and should be delivered patient-centered services.